Transformational Leadership and Lecturer Performance in Islamic Higher Education: The Mediating Role of Self-Efficacy - Jumira Warlizasusi; Zulhimma Zulhimma; Elfridawati Mai Dhuhani; Eka Prasetiawati; Ruslina Dwi Wahyuni; Ifnaldi Ifnaldi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of transformational leadership and self-efficacy in explaining lecturer performance in fulfilling the Tri Dharma of higher education, namely teaching, research, and community service. Using a quantitative survey design, data were collected from 112 lecturers at IAIN Curup through a structured questionnaire measuring transformational leadership, self-efficacy, and lecturer performance. The data were analysed using regression-based simple mediation analysis to test the direct effect of transformational leadership on lecturer performance and its indirect effect through self-efficacy. The findings show that transformational leadership had a small positive direct effect on lecturer performance (β = 0.150, p = 0.037), and self-efficacy had a small positive effect on lecturer performance (β = 0.198, p = 0.042). Transformational leadership had a weak positive effect on self-efficacy (β = 0.154, p = 0.039). The indirect effect through self-efficacy was very small (β = 0.030), although the bootstrapped 95% confidence interval did not include zero. These results indicate that self-efficacy functions as a statistically supported but practically limited mediator. The study contributes to Islamic education management by showing that transformational leadership and self-efficacy remain relevant in Indonesian Islamic higher education. Still, their explanatory power is limited without broader institutional variables such as workload, governance, research support, and professional development. However, the study is limited by its single-institution cross-sectional design and reliance on self-reported data. Future research should implement longitudinal or mixed-method designs across multiple institutions, using structural equation modelling to test comprehensive moderated-mediation frameworks that explicitly integrate macro-organisational variables such as workload distribution, institutional governance, publication support, and administrative constraints.